Strategi Pengembangan Bisnis dalam Meningkatkan Keunggulan Bersaing pada Usaha Kuliner Mie Ayam Mbah Bejo Kecamatan Genteng, Banyuwangi - Arik Lailatul Maghfiroh; Mohammad Mirza Pratama (Lembaga Yasin AlSys, 2026)
Although competition in the culinary business is becoming increasingly intense, studies that specifically discuss business development strategies in local culinary businesses to enhance competitive advantage remain relevant. This study aims to analyze the business development strategies implemented by the Mie Ayam Mbah Bejo culinary business in Genteng Subdistrict, Banyuwangi, in improving its competitive advantage in the local culinary market. This study used a qualitative approach with a descriptive method. Data were collected through interviews, observation, and documentation involving the business owner, employees, and customers of Mie Ayam Mbah Bejo, and were then analyzed through data reduction, data display, and conclusion drawing. The results showed that the business development strategy was implemented through the marketing concept of Segmenting, Targeting, and Positioning (STP) and Strengths, Weaknesses, Opportunities, and Threats (SWOT) analysis. In terms of segmentation, the business did not limit customers by region, age, or income level, thereby reaching various segments of society. The targeting strategy was open by making all levels of society the target market, while positioning was built through the image of a legendary chicken noodle stall with a distinctive taste, affordable prices, a strategic location, and friendly service. The SWOT analysis showed that the business’s strengths lie in product quality, affordable prices, a strategic location, and the utilization of digital technology, such as delivery services and cashless payments. The opportunities include the development of digital technology and the business reputation that has been widely recognized, while the business’s weaknesses include limited workforce and environmental conditions prone to flooding, and the threats stem from increasing competition from similar culinary businesses and changes in consumer preferences. Thus, this study confirms that the implementation of appropriate business development strategies contributes to enhancing the competitive advantage and sustainability of the Mie Ayam Mbah Bejo business amid competition in the local culinary market.